Functional Movement Screen at DKI Jakarta POPB Athletics in 2023 - Ramadani, Ermyka Elma Elma; Setiakarnawijaya, Yasep; Kuswahyudi, Kuswahyudi (Universitas Negeri Semarang, 2023)
Functional Movement Screen (FMS) is a method for assessing a person's functional movement abilities. FMS can be used as a screening and injury prevention effort. The aim of this research is to provide information on weaknesses in functional movement patterns, FMS provides information on asymmetries and limitations in functional movement patterns between right and left and FMS helps predict the risk of injury that may occur. FMS consists of 7 movements, namely: (1) Deep Squat, (2) Hurdle Step, (3) Inline Lunges, (4) Shoulder Mobility, (5) Active Straight Leg Raise, (6) Trunk Stability Push Up, and (7) Rotary Stability. This research is quantitative descriptive. By using observation techniques to collect information. This research involves the use of tools, instruments and procedures to collect objective and systematic data. In this research, the 2023 Jakarta popb athletics athletes were involved with a total sample of 13 athletes. The results of this research show that the FMS profile of POPB DKI Jakarta athletic athletes in 2023 is 1 athlete showing points 21, namely a perfect score, 7 athletes showing points 17-20, namely good, 3 athletes showing points 14-16, namely inefficient. The average profile of POPB DKI Jakarta athletic athletes in 2023 is in good condition.